Risk indicators for increased periodontal probing depth in subjects attending a public dental school in Brazil - Silva-Boghossian, Carina M; Luiz, Ronir; Colombo, Ana Paula (Oral health & preventive dentistry, 2011)
To assess the prevalence, extent and severity of periodontal probing depth (PD) and their association with sociodemographic and behavioural parameters in subjects attending a public dental school in Brazil. Five hundred and fifty-nine consenting participants (18 to 77 years of age) were submitted to full-mouth periodontal clinical examination and anamnesis questionnaires. The data were analysed by multivariable models using logistic regression analyses. The dependent variables were moderate (≥ 5 mm in ≥ 10% of sites) and deep (≥ 7 mm in at least one site) PD. The prevalence of individuals with at least one site with PD ≥ 5 mm or ≥ 7 mm was 69% and 54%, respectively. Mean PD ranged from 2.86 to 3.08 mm, and the mean frequency of sites with moderate and deep PD ranged from 10.74% to 14.99%, and from 4.60% to 5.36%, respectively, according to age. Multivariate analyses identified a higher risk for having PD ≥ 5 in ≥ 10% of sites and 7 mm in at least one site in smokers (odds ratio [OR] = 10.56 and 9.10, respectively), and the presence of >10% of sites with bleeding on probing (BOP) (OR = 6.37 to 20.91, and 6.94 to 26.19, respectively). Age 36 to 50 years (OR = 1.95) and >50 years (OR = 3.15), presence of >30% of sites with supragingival biofilm (SB) (OR = 2.80), and ≥ 4 missing teeth (OR = 2.26) were risk indicators for PD ≥ 7 mm in at least one site. This particular Brazilian population presented high prevalence and extent of increased periodontal probing depth. Age, smoking, BOP, SB, and tooth loss were risk indicators associated with probing depth in these individuals.